Involvement work systems and operational effectiveness: Exploring the moderating effect of national power distance - Jiang, Yuan; Colakoglu, Saba; Lepak, David P; Blasi, Joseph R; Kruse, Douglas L (Journal of International Business Studies, 2015)
Work practices that involve employees are generally assumed to be less effective in more hierarchical societies where employees’ values are not aligned with such practices. In this study, we challenge this assumption by developing a theory that differentiates between the symbolic and instrumental aspects of involvement work systems and proposing that their symbolic impact will be more pronounced in egalitarian societies, whereas their instrumental impact will be more pronounced in hierarchical societies. In particular, we draw on the symbolic action perspective and theories on culture to test the relationship between involvement work systems and operational effectiveness by incorporating organizational climate of participation and national cultural differences in power distance. Using multi-source, multilevel data from 260 facilities of a multinational company operating in 22 countries, we found that the mediated relationship between involvement work systems and operational effectiveness through climate of participation (i.e., the symbolic impact) was stronger among facilities located in lower power distance societies. On the other hand, the direct relationship between involvement work systems and operational effectiveness (i.e., the instrumental impact) was stronger in higher power distance societies. Overall, our study resolves a seeming cultural dilemma with regard to how involvement work systems operate cross-culturally.